Determinants of People’s Secondary Hazards Risk Perception: A Case Study in Wenchuan Earthquake Disaster Areas of China - Huang, Huan; Wang, Rui; Xiao, Yi; Li, Yuan; Zhang, Qiu-Feng; Xiang, Xin (Frontiers in Earth Science, 2022)
Few studies have examined people's subjective perceptions of risk after secondary disasters. This study selected 12 towns in the areas where secondary geological hazards (SGH) occurred after the Wenchuan earthquake as the survey research areas and obtained a total of 957 valid samples to assess the risk perceptions of residents and the factors influencing them ten years after the disaster. Using four indicators (possibility, awareness, apprehension, and impact) to construct the Resident Risk Perception Index (RRPI), the results show that residents in the affected areas have high, moderate, and low-risk perceptions of SGH at 27.59%, 48.38%, and 24.03% respectively. The study found that people who suffered in the past from geological disasters had a higher risk perception. Perceptions of secondary geological hazard risk varied significantly with age, education, marital status, and experience. It was also found that residents in the 30-40 age group have the highest risk perception, young people in the 20-30 age group have the highest risk awareness, and older people over 60 are more fearful of SGH. The study recommends awareness campaigns and adequate disaster preparedness exercises to improve the risk perception of local people, especially to foster ownership of learning about disasters among residents.